Immobilized cells : basics and applications : proceedings of an international symposium organized under auspices of the Working Party on Applied Biocatalysis of the European Federation of Biotechnology, Noordwijkerhout, the Netherlands, November 26-29, 1995 /: basics and applications : proceedings of an international symposium organized under auspices of the Working Party on Applied Biocatalysis of the European Federation of Biotechnology, Noordwijkerhout, the Netherlands, November 26-29, 1995. (1996) - Unknown
No abstract available